PANDANGAN HUKUM ISLAM TERHADAP TRADISI PERNIKAHAN DI DEPAN JENAZAH KELUARGA (Studi Interaksi Budaya Dan Agama Di Desa Bocek Kecamatan Karangploso Kabupaten Malang) - Hikmatun Balighoh Al Ula; Moh. Murtadlo; Syamsu Madyan (Jurnal Hikmatina, 2019)
Marriage in Islam is a worship that is performed to follow the sunnah of the Prophet Muhammad. Allah created humans of different types, namely men and women who are none other than all that aims so that humans can live in pairs by doing a marriage in order to get offspring. Not only Islamic Law that governs a marriage in terms of harmony and conditions By the way, other religions also regulate marriage. Not only does the state regulate marriage laws, traditions or customs in the community, it also does not miss regulating a marriage in the community. Like the tradition of marriage in front of the body of one of the families who died that occurred in Bocek village, Karangploso sub-district, Malang district. The tradition was carried out because before the day and date of the wedding were determined, one family died and had to do the tradition if they did not want the marriage to be postponed for 1 year. Kata Kunci: Pandangan Hukum Islam, Tradisi, Pernikahan di depan jenazah Marriage in Islam is a worship that is performed to follow the sunnah of the Prophet Muhammad. Allah created humans of different types, namely men and women who are none other than all that aims so that humans can live in pairs by doing a marriage in order to get offspring. Not only Islamic Law that governs a marriage in terms of harmony and conditions By the way, other religions also regulate marriage. Not only does the state regulate marriage laws, traditions or customs in the community, it also does not miss regulating a marriage in the community. Like the tradition of marriage in front of the body of one of the families who died that occurred in Bocek village, Karangploso sub-district, Malang district. The tradition was carried out because before the day and date of the wedding were determined, one family died and had to do the tradition if they did not want the marriage to be postponed for 1 year. Kata Kunci: Pandangan Hukum Islam, Tradisi, Pernikahan di depan jenazah